Forum Bildverarbeitung 2020 - Heizmann, Michael; Längle, Thomas (KIT Scientific Publishing, 2020)
Image processing plays a key role for fast and contact-free data acquisition in many technical areas, e.g., in quality control or robotics. These conference proceedings of the "Forum Bildverarbeitung", which took place on 26.-27.11.202 in Karlsruhe as a common event of the Karlsruhe Institute of Technology and the Fraunhofer Institute of Optronics, System Technologies and Image Exploitation, contain the articles of the contributions.